2020
DOI: 10.15761/tec.1000206
|View full text |Cite
|
Sign up to set email alerts
|

Virtual anatomy and pathoanatomy: Cinematic rendering of a traumatic brain injury

Abstract: Figure 3. In cinematic rendering, the combination of path-tracing methods and a global illumination model allows a lifelike display of the affected areaFigure 4. The combination of photorealistic display and a clear depiction of the entire anatomical region increases pathology conspicuity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The demonstration of pathoanatomical cases (Figure 2) facilitates the recognition and learning of relevant clinical structures in terms of clinical anatomy and increases the compliance of the students to deal intensively with the sometimes very dry subject. Initial experience has already shown that the cinematic rendering of CT data sets allows excellent visualization of bone and vascular structures, which conventional cadaver-based anatomy cannot achieve in this form [15][16][17][18][19][20][21][22][23][24], see Figures 3 and 4. Other structures, such as nerves and fasciae, have not yet been able to be adequately represented using radiological methods.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration of pathoanatomical cases (Figure 2) facilitates the recognition and learning of relevant clinical structures in terms of clinical anatomy and increases the compliance of the students to deal intensively with the sometimes very dry subject. Initial experience has already shown that the cinematic rendering of CT data sets allows excellent visualization of bone and vascular structures, which conventional cadaver-based anatomy cannot achieve in this form [15][16][17][18][19][20][21][22][23][24], see Figures 3 and 4. Other structures, such as nerves and fasciae, have not yet been able to be adequately represented using radiological methods.…”
Section: Discussionmentioning
confidence: 99%